Prevalence and Clinical Signs of Postpartum Dysgalactia Syndrome at The First Day after Farrowing in Farmed Sows in The Republic of Macedonia - Angjelovski, Branko; Radeski, Miroslav; Djadjovski, Igor; Mitrov, Dine; Bojkovski, Jovan; Adamov, Nikola; Dovenski, Toni; Dzadzovski, Igor (Walter de Gruyter GmbH, 2019)
Abstract The objective of the present study was to determine the prevalence of postpartum dysgalactia syndrome (PDS) and associated clinical signs in farmed sows in the Republic of Macedonia (RM) in the first 12-24 h postpartum. A total of 202 sows of different parity and different genetic lines from 5 pig farms in RM were included in the study. The sows and their litters were clinically examined 12-24 hours after farrowing. Postpartum dysgalactia syndrome was detected in 23.3% of all clinically examined sows, while prevalence between farms ranged from 14.8% to 38.1%. Altered piglet’s behavior was the most frequent clinical pattern observed in 68.1% of the PDS–affected (PDSA) sows. Regarding the clinical signs in PDSA sows detected among farms, significant differences were observed in the altered piglet’s behavior (p<0.05) and hypogalactia (p<0.05). Endometritis was more often detected in older sows (90%) compared to endometritis in younger animals (44.4%). In addition, fever was also more frequently diagnosed in higher parity (≥3 parity) sows (55.0%) in contrast to other PDSA sows (22.2%). This study has demonstrated the presence of PDS in farmed sows in RM. High frequency of altered piglet’s behavior found in this study could be an useful indicator for early detection of lactation problems in sows. Frequent pathological vaginal discharge in older sows indicates that endometritis plays an important role in the clinical manifestation of PDS. Further investigations should be conducted in order to identify specific risk factors associated with clinical PDS in farmed sows in RM.